2015
DOI: 10.1111/andr.12111
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of early outcomes after a single‐armed suture technique for microsurgical intussusception vasoepididymostomy

Abstract: SUMMARYLongitudinal intussusception microsurgical vasoepididymostomy (LIVE) increases the patency rate in men with epididymal obstructive azoospermia (EOA). Here, we retrospectively analyzed the early outcomes of our modified single-armed suture technique for LIVE in men with EOA. From February 2012 to November 2013, 51 men received the modified technique and 39 men provided at least one post-operative semen sample. The mean age was 31.4 years old for the men and 29.2 years old for their female partners. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…The epididymis is an important organ of the male excurrent ductal system where spermatozoa acquire forward motility and fertilisation capacity (Mahmoud et al, ). The presence of non‐motile spermatozoa in the epididymis of patients with EOA may indicate a spermatozoa defect or epididymal dysfunction (Zhao et al, ). Therefore, patency and pregnancy rates are higher when motile spermatozoa are found in the epididymis at the anastomosis site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epididymis is an important organ of the male excurrent ductal system where spermatozoa acquire forward motility and fertilisation capacity (Mahmoud et al, ). The presence of non‐motile spermatozoa in the epididymis of patients with EOA may indicate a spermatozoa defect or epididymal dysfunction (Zhao et al, ). Therefore, patency and pregnancy rates are higher when motile spermatozoa are found in the epididymis at the anastomosis site.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ICSI is often expensive for patients, particularly individuals in developing countries. With the development of microsurgery, vasoepididymostomy has been shown to be a more cost‐effective treatment option for epididymal obstructive azoospermia (EOA), with good outcomes (Peng, Zhang, Yuan, Cui, & Song, ; Zhao et al, ). The patency rates following treatment reportedly range from 48% to 92%, with natural pregnancy rates ranging from 4.17% to 40% (Chan, Brandell, & Goldstein, ; Hong et al, ; Kumar, Mukherjee, & Gupta, ; Peng et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…MVE techniques have continued to evolve and improve since 1998, with LIVE becoming the gold standard. 4 5 6 7 15 16 17 18 19 In our previous studies, we described a modified single-armed suture technique for LIVE and achieved a patency rate of 61.5% in men with epididymal obstructive azoospermia. 5 6 …”
Section: Discussionmentioning
confidence: 99%
“… 4 Monoski et al 5 from Weill Cornell Medicine of Cornell University (New York, NY, USA) first reported the single-armed suture LIVE technique in a rat model, while our group first pioneered a modified single-armed suture human LIVE technique and achieved an early 6-month patency rate of 61.5%. 6 7 This novel single-armed suture LIVE technique is especially suitable for surgeons in areas without specialized double-armed sutures.…”
Section: Introductionmentioning
confidence: 99%
“…Small modifications of the LIVE technique have been described in the literature. The use of single-armed 10-0 sutures has been evaluated in several trials (62)(63)(64)(65). The resulting patency rates using a single-armed 10-0 tended to be less than with the use of a traditional double-armed suture.…”
Section: Vasoepididymostomymentioning
confidence: 99%